Ursolic acid and carvacrol may be potential inhibitors of dormancy protein small heat shock protein16.3 of Mycobacterium tuberculosis. Issue 13 (3rd October 2018) - Jee, Babban; Kumar, Sanjay; Yadav, Renu; Singh, Yogesh; Kumar, Anuj; Sharma, Naveen
Abstract : Small heat shock protein16.3 (sHSP16.3) is a crucial protein for survival of Mycobacterium tuberculosis (MTB) in its host. Besides, this protein acts as a molecular chaperone during stress and is indispensable for MTB's growth, virulence and cell-wall thickening. sHSP16.3 is also a promising candidate for vaccine, serodiagnosis and drug design as well. In the present study, we have targeted sHSP16.3 with two phytochemicals, namely ursolic acid and carvacrol using in silico approach. Molecular docking analysis showed that both phytochemicals (ursolic acid and carvacrol) have docked with sHSP16.3 and shown tendency to inhibit the function of this vital protein of MTB. In addition, both compounds have exhibited strong compatibility with sHSP16.3 during whole 60 ns duration of molecular dynamics simulation. Further, the molecular mechanic/generalized Born/Poisson–Boltzmann surface area (MM/G/P/BSA) free energies were calculated which showed that both phytocompounds have stable and favourable binding energies causing strong binding with binding site of sHSP16.3. Taking together, the data of present study suggest that both phytocompounds may be potential inhibitor of sHSP16.3 of MTB and a best alternative to standard anti-tuberculosis drugs.